Lung inflammation in COPD: why does it matter? - Oh, Jin Young (Faculty of 1000 Ltd, 2012)
COPD is characterized by lung inflammation, which intensifies with disease progression. Recent studies suggest that COPD has multiple phenotypes, each with a distinct molecular pathway. Proteolytic enzymes may have a prominent role in the emphysematous phenotype, while nitric oxide pathways may be more relevant for pulmonary vessel remodelling in COPD. This article provides a synopsis of the possible role that lung inflammation plays in the pathogenesis of COPD.